Improving CAR-T immunotherapy: Overcoming the challenges of T cell exhaustion - Gumber, Diana; Wang, Leo D. (EBioMedicine, 2022)
Chimeric antigen receptor (CAR) T cell therapy has emerged as a cancer treatment with enormous potential, demonstrating impressive antitumor activity in the treatment of hematological malignancies. However, CAR T cell exhaustion is a major limitation to their efficacy, particularly in the application of CAR T cells to solid tumors. CAR T cell exhaustion is thought to be due to persistent antigen stimulation, as well as an immunosuppressive tumor microenvironment, and mitigating exhaustion to maintain CAR T cell effector function and persistence and achieve clinical potency remains a central challenge. Here, we review the underlying mechanisms of exhaustion and discuss emerging strategies to prevent or reverse exhaustion through modifications of the CAR receptor or CAR independent pathways. Additionally, we discuss the potential of these strategies for improving clinical outcomes of CAR T cell therapy.